Case Report: Hemophagocytic lymphohistiocytosis associated with NBAS gene variant and Epstein-Barr virus (EBV) infection - Zhao, Jing; Chen, Xilong; Yue, Shixia (Frontiers in Pediatrics, 2025)
Hemophagocytic syndrome (HPS), also known as hemophagocytic lymphohistiocytosis (HLH), is a life-threatening disorder that can occur in both children and adults, closely associated with genetic factors and acquired immune dysregulation. This article presents a case report of HLH with NBAS gene mutation and chronic active Epstein–Barr virus (EBV) infection. Despite undergoing a series of aggressive treatments, the patient failed to achieve a favorable clinical response. The clinical course was complicated by hepatic injury, coagulopathy, progressive cytopenia in all three blood cell lineages, and significant elevation of serum ferritin, ultimately resulting in fatal outcome. Current research on genetic predisposing factors has identified 17 causative genes for HLH, including PRF1 and UNC13D. However, NBAS-related cases have been rarely reported. The discovery of additional potential pathogenic genes holds significant value for advancing diagnostic and therapeutic approaches in HLH management.